Variability in seedling emergence for European and North American populations of Abutilon theophrasti. (3rd December 2018) - Loddo, D; Bozic, D; Calha, I M; Dorado, J; Izquierdo, J; Šćepanović, M; Barić, K; Carlesi, S; Leskovsek, R; Peterson, D; Vasileiadis, V P; Veres, A; et al.
Summary: Abutilon theophrasti is a weed that is spreading worldwide and that has had to adapt to different combinations of environmental conditions. Wide interpopulation variability has been reported regarding dormancy and germination. This variability, controlled by the interaction of genetic diversity and maternal effect, could hinder the adoption of Integrated Weed Management (IWM) tools. A collaborative project was conducted to compare emergence dynamics of 12 European and North American populations under diverse environmental conditions. The main aim was to assess interpopulation variability and explain this according to environmental conditions in the seed collection sites. Seeds were sown at six experimental sites, and seedling emergence was monitored. The AlertInf model was tested to evaluate its ability to predict emergence dynamics of the different populations. A wide interpopulation variability was observed for emergence percentage and dynamics with consistent trends across sites and related to different seed dormancy levels. Populations from Catalonia, Iowa and Minnesota reached higher emergence percentage with earlier and concentrated emergence flushes probably due to low dormancy level, while populations from Croatia, Serbia and Hungary, given their low average emergence percentage, presented high dormancy levels. Good predictive accuracy of AlertInf model was obtained at the different sites, confirming the possibility of adopting it across a wide range of environmental conditions. Achieving a better knowledge of interpopulation variability can allow specific control strategies to be designed, facilitating the replacement of solely herbicide‐based management with true IWM.